E2F1: Cause and Consequence of DNA Replication Stress - Fouad, Shahd; Hauton, David; D'Angiolella, Vincenzo (Frontiers in Molecular Biosciences, 2021)
Cell cycle entry in mammalian cells occurs in response to the correct stimuli and is promoted by the transcriptional activity of E2F family members. E2F proteins regulate the transcription of S phase cyclins and genes required for DNA replication, DNA repair and apoptosis. The activity of E2F1, the archetypal and most heavily studied E2F family member, is tightly controlled by the checkpoint to modulate cell cycle progression and to initiate programmed cell death when required. Altered tumor suppressor and oncogene pathways often result in direct or indirect interference with E2F1 regulation to ensure higher rates of cell proliferation independently of external cues. Despite a clear link between dysregulated E2F1 activity and cancer progression, literature on the contribution of E2F1 to DNA replication stress phenotypes is somewhat scarce. This review emphasizes how dysfunctional tumor suppressor and oncogene pathways promote the disruption of E2F1 transcription and hence of its transcriptional targets, and how such events have the potential to drive DNA replication stress. In addition to the involvement of E2F1 upstream of DNA replication stress, this manuscript also discusses the role of E2F1 as a downstream effector of the response to this type of cellular stress. Lastly, this review introduces some reflections on how E2F1 activity is integrated with checkpoint control through post-translational regulation, and proposes an exploitable tumor weakness based on this axis.